2009
DOI: 10.1111/j.1365-2044.2009.06084.x
|View full text |Cite
|
Sign up to set email alerts
|

An observational cohort study of triage for critical care provision during pandemic influenza: ‘clipboard physicians’ or ‘evidenced based medicine’?

Abstract: SummaryWe assessed the impact of a United Kingdom government‐recommended triage process, designed to guide the decision to admit patients to intensive care during an influenza pandemic, on patients in a teaching hospital intensive care unit. We found that applying the triage criteria to a current case‐mix would result in 116 of the 255 patients (46%) admitted during the study period being denied intensive care treatment they would have otherwise received, of which 45 (39%) survived to hospital discharge. In tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 17 publications
1
43
1
1
Order By: Relevance
“…The admission STSS (Table 3) and initial SOFA (Table 4) scores were calculated and compared against actual mortality, need for ICU admission, and need for MV. The performance of STSS and SOFA in our subset is compared with the figures quoted in the original reports [9,13], in which the ROC AUC results were used to assess the performance of the individual score groupings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The admission STSS (Table 3) and initial SOFA (Table 4) scores were calculated and compared against actual mortality, need for ICU admission, and need for MV. The performance of STSS and SOFA in our subset is compared with the figures quoted in the original reports [9,13], in which the ROC AUC results were used to assess the performance of the individual score groupings.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical course of H1N1 pandemic influenza has not occurred as expected. As data has become accessible, reports suggest that SOFA score may not be a good discriminator of outcome in this cohort of patients [12,13]. Thus, its suitability as a means to assist in the triage of H1N1 patients has been called into question.…”
Section: Introductionmentioning
confidence: 99%
“…This plan used the SOFA score combined with a list of inclusion and exclusion criteria for admission to the critical care unit as a triage tool to complement clinical judgment. Nevertheless, Guest et al [21 ] found that applying the SOFA triage criteria to a current case-mix would result in 116 of the 255 patients (46%) admitted during the study period being denied intensive care treatment they would have otherwise received, of which 45 (39%) survived to hospital discharge. The conclusion was that the proposed triage tool failed adequately to prioritize patients who would benefit from intensive care.…”
Section: Triagementioning
confidence: 99%
“…Findings of a recent pilot study suggest that the application of a SOFA-based critical care triage protocol could direct scarce resources to patients who are most likely to benefit from them and increase resource availability [28]. However, another study did not share this finding [29]. …”
Section: Concepts Of Operationsmentioning
confidence: 99%